Hospitality Venues’ Anti-tobacco Legislation Violation in 11 Different Cities in Türkiye - Dilek Aslan; Yağmur Ünal; Sevinç Sütlü; Raika Durusoy; Mahmut Talha Uçar; Evrim Arslan; Elçin Balcı; Elif Sızan; Beyza Püren Selcan Gündoğdu; Emir Atasoy; Şeyma Duman; Selma Karabey; et al. (Thoracic Research and Practice)
OBJECTIVE: In Türkiye, anti-tobacco legislation (Law No. 4207 on the Prevention and Control of Harms of Tobacco Products) aims to ensure a “tobacco-free” life for current and future generations. Thus, there are observations of violations in the hospitality sector. In this study, we aimed to observe the status of hospitality venues’ violation of the law in 11 different cities in Türkiye. MATERIAL AND METHODS: This descriptive study examined 772 hospitality venues in Ankara, Burdur, Diyarbakır, Giresun, Hatay, İstanbul, İzmir, Kars, Kayseri, Samsun, and Zonguldak between August 1 and October 10, 2023. The Google Forms survey, Microsoft Excel, and IBM SPSS Statistics (Version 23) programs were used for data collection, entry, and analysis. A logistic regression model was used to understand the associations between non-compliance and the characteristics of the venues. RESULTS: During the observation of indoor spaces, tobacco products were used in 282 venues (37.1%). Non-compliance in bars, pubs, traditional coffee houses, and hookah cafes was statistically significantly higher than in the other venue types [odds ratio (OR)= 3.031, 95% confidence interval (CI): 1.699 to 5.408, P < 0.001]. The presence of a retractable roof and/or side wall (OR=5.362, 95% CI: 3.518 to 8.173, p < 0.001), later hour observations (OR= 2.120, 95% CI: 1.399 to 3.212, p < 0.001), and the existence of outdoor venues where smoking is permitted (OR= 3.165, 95% CI: 2.170 to 4.617, p < 0.001) also increased indoor violations. CONCLUSION: The findings provided scientific evidence that violations of Turkish anti-tobacco legislation exist in hospitality venues. The public authorities are advised to play their vital role in preventing violations in indoor spaces.